(untitled) (International relations and international law Journal, 2016)
The paper addresses the issue of the country’s image from a perspective, aiming to identify and analyze the ways in which cultural diplomacy can support the branding process. The article discusses the role of cultural diplomacy in promoting Italy’s positive image abroad. The article explores Italian application of soft power through culture and language promotion, and cultural tourism. The analysis was conducted by assessing official documents. The author stresses that the instruments of cultural diplomacy are not fully supported in promoting the image of Italy in the world’s communication channels, and it reduces the efficiency of image policy. Such problems as the absence of unified strategy, combining the various initiatives of ministries and departments at central and regional levels, and funding restrictions obstruct to effective application of soft power instruments